2022
DOI: 10.1186/s12903-022-02187-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root canal morphology in permanent maxillary and mandibular anterior teeth in Saudi subpopulation using two classification systems: a CBCT study

Abstract: Background Adequate knowledge of root canal morphology and possible variations is essential to achieve perfect root canal treatment and overcome treatment failure. Appropriate knowledge on root and canal morphology, communication, and documentation amongst dentists will be challenging from a diagnostic and successful treatment point of view. Methods A total of 3420 samples were included in this study from 285 cone-beam computed tomography images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…41,49,50 Conversely, few local original studies have investigated canine morphology. 2,3,[29][30][31][32][33] Maxillary canines usually have one root and one canal and rarely have two roots or two channels. This condition explains local or/and international case reports involving maxillary canines with double roots or canals are few.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…41,49,50 Conversely, few local original studies have investigated canine morphology. 2,3,[29][30][31][32][33] Maxillary canines usually have one root and one canal and rarely have two roots or two channels. This condition explains local or/and international case reports involving maxillary canines with double roots or canals are few.…”
mentioning
confidence: 99%
“…43,[45][46][47][48] Other studies reported mandibular canines with two canals and two roots. 41,42,44,49,50 Among the Saudi population, quite a few number of peer-reviewed original studies and research 2,3,[29][30][31][32][33] or case reports [41][42][43][44][45][46][47][48][49][50] have investigated the RMCC of permanent canine as shown in Table 1. Most other original research studies that investigated the canine has been conducted outside the Saudi population [20][21][22][23][24][25][26][52][53][54][55][56][57][58][59][60] as presented in Table 2.…”
mentioning
confidence: 99%
“…Various techniques to analyze the structure of the root canal include tooth clearing technique, tooth sectioning, conventional radiography, CBCT, and micro-computed tomography (micro CT) [ 10 ]. However, tooth clearing and sectioning can be useful for in-vitro studies, and they are not typically performed in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…5 In 2017, Ahmed et al 6 introduced a coding system to overcome shortcomings of previous classifications, such as inaccurate characterization of the root and inability to classify complex root canal anatomy, which has been evidenced in several laboratory and clinical studies. [5][6][7][8][9][10][11] This system includes codes for the number of teeth, the number of roots, and the different types of root canal morphology. This classification system for root and canal morphology has been implemented in both clinical and academic research settings 12,13 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%